Cardiac troponin I: is it a marker to detect cardiotoxicity in children treated with doxorubicin? - Köseoğlu, Vedat; Berberoğlu, Semha; Karademir, Selmin; Kısmet, Erol; Yurttutan, Neval; Demirkaya, Erkan; Sungur, Metin; Alehan, Dursun (The Turkish Journal of Pediatrics, 2005)
Doxorubicin has been used in the the treatment of malignant tumors in children. Its use is limited by cardiotoxic effects beyond a cumulative dose of 450 mg/m2. To detect cardiotoxicity at an early stage and identify patients at risk for development of cardiotoxicity are matters of concern. Recently, cardiac troponin I (cTnI) has been reported to be useful for detecting minor myocardial damage. In the present study, we investigated whether cumulative doxorubicin-related myocardial cell damage can potentially increase cTnI levels above the expected values in 22 patients treated with cumulative doxorubicin doses of 120 to 450 mg/m2. Impaired cardiac functions were found in three patients by echocardiography, but serum CTnI levels were within the ranges expected in healthy individuals both in patients with cumulative doxorubicin doses > or = 400 mg/m2 and in patients with disturbed cardiac functions. We found no relationship between serum cTnI, cumulative dose of doxorubicin, and echocardiographical findings.